2020
DOI: 10.1038/s41467-020-17758-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular architecture and activation of the insecticidal protein Vip3Aa from Bacillus thuringiensis

Abstract: Bacillus thuringiensis Vip3 (Vegetative Insecticidal Protein 3) toxins are widely used in biotech crops to control Lepidopteran pests. These proteins are produced as inactive protoxins that need to be activated by midgut proteases to trigger cell death. However, little is known about their three-dimensional organization and activation mechanism at the molecular level. Here, we have determined the structures of the protoxin and the protease-activated state of Vip3Aa at 2.9 Å using cryo-electron microscopy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
92
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(109 citation statements)
references
References 63 publications
(90 reference statements)
8
92
2
Order By: Relevance
“…After trypsinization, all four monomers stay connected, and no conformational change takes place in domains II to V. Three N-terminal α helices form a parallel four helix coiled coil, which forms a long dipole to lodge the ions in its cavity. Its dimension has the ability to form pores in the lipid bilayer [47].…”
Section: Structure and Function Of Vip3 Proteinsmentioning
confidence: 99%
“…After trypsinization, all four monomers stay connected, and no conformational change takes place in domains II to V. Three N-terminal α helices form a parallel four helix coiled coil, which forms a long dipole to lodge the ions in its cavity. Its dimension has the ability to form pores in the lipid bilayer [47].…”
Section: Structure and Function Of Vip3 Proteinsmentioning
confidence: 99%
“…Thus, this architecture revealed that tetramer of Vip3 protoxin assembled into pyramid shape having N-terminal apex and core, and C-terminal exposed toward solvents (Núñez-Ramírez et al, 2020). The structure-comparison analysis of Vip3A and Vip3B revealed that both proteins have similar tetrameric organization shares a significant similarity between domains I, II, and III and the analogous relationship between the flexible domains IV and V as they are responsible for exposing of glycan-binding side toward solvent (Núñez-Ramírez et al, 2020;Zheng et al, 2020).…”
Section: Vip 3 Proteins: Structurementioning
confidence: 93%
“…Recently, another new high-resolution 3D-structures of complete protoxin and activated Vip3Aa protein conformations were analyzed through Cryo-electron microscopy at 2.9 Å by Núñez-Ramírez et al (2020). The domain organization of protoxin Vip3 revealed five domains in the protoxin (Figure 4), which are following: Domain I (1-199aa): It is composed of highly curved four (α1-α4) helices that look like pyramid apex and validated as protease cleavage site.…”
Section: Vip 3 Proteins: Structurementioning
confidence: 99%
“…However, thus far no resistance to Vip proteins has been reported (Tabashnik and Carrière, 2017; Tabashnik and Carrière, 2020). Although Cry and Vip toxins affect the same cells in the larval midgut tissue, these proteins have no structural homology and bind to different receptors in the larval midgut (Lee et al ., 2003; Wang et al ., 2018; Núñez‐Ramírez et al ., 2020), and no cross‐resistance has been observed between these two proteins (Carrière et al ., 2015; Chakroun et al ., 2016a,b).…”
Section: Introductionmentioning
confidence: 99%